2019
DOI: 10.1007/s13105-019-00706-3
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of AMP-activated protein kinase in insulin-secreting β cells: a potential target for improving β cell function?

Abstract: AMP-activated protein kinase (AMPK) is present in different kinds of metabolically active cells. AMPK is an important intracellular energy sensor and plays a relevant role in whole-body energy homeostasis. AMPK is activated, among others, in response to glucose deprivation, caloric restriction and increased physical activity. Upon activation, AMPK affects metabolic pathways leading to increased formation of ATP and simultaneously reducing ATP-consuming processes. AMPK is also expressed in pancreatic β cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…In the same study, transplantation of islets expressing the constitutively active AMPK into streptozotocin-induced diabetic mice improved glycemic control less effectively than transplantation with control islets. In contrast, other studies concluded that activation of AMPK by AICAR increases insulin secretion [4,5]. The effects of AMPK on glucose-stimulated insulin secretion may be influenced by experimental conditions, such as the glucose concentrations in cell culture media and during the insulin secretion assays.…”
Section: Ampk In the β-Cellmentioning
confidence: 97%
See 2 more Smart Citations
“…In the same study, transplantation of islets expressing the constitutively active AMPK into streptozotocin-induced diabetic mice improved glycemic control less effectively than transplantation with control islets. In contrast, other studies concluded that activation of AMPK by AICAR increases insulin secretion [4,5]. The effects of AMPK on glucose-stimulated insulin secretion may be influenced by experimental conditions, such as the glucose concentrations in cell culture media and during the insulin secretion assays.…”
Section: Ampk In the β-Cellmentioning
confidence: 97%
“…Intuitively, activation of AMPK in the β-cell should not accompany the stimulatory action of glucose on insulin secretion, the former resulting from low energy state and the latter being associated with robust ATP production. However, the numerous studies on these actions are somehow contradictory, as extensively reviewed by others [4,5]. Here, we will address the effects of metabolic stresses on the expression of the key components of the AMPK system.…”
Section: Ampk and Glucose Homeostasismentioning
confidence: 98%
See 1 more Smart Citation
“…AMPK, as the main target of metformin, regulates the function of hepatic glucose metabolism and pancreatic b-cell [8,11,26]. It has been widely agreed that the phosphorylation of AMPK is induced by metformin, although the speci c route is not clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we review how the activities of the endoplasmic reticulum (ER), mitochondria, lysosomes, and autophagosomes within β -cells are influenced by chronic and sustained stimulation of two key nutrient-sensor proteins, the mechanistic target of rapamycin (mTOR) and O-linked N-acetylglucosamine transferase (OGT), and how these changes contribute to systemic β -cell failure. The catabolic nutrient sensor AMP-activated protein kinase (AMPK) is also important for β -cell function, and AMPK signaling is perturbed during T2D [ 8 , 9 ]. However, AMPK and organelle homeostasis in β -cells is understudied; this is a subject greatly in need of further research.…”
Section: Introductionmentioning
confidence: 99%